Spillover Effects of Stock Options Trading on the Volatility of Underlying Stocks - Ganai, Dr. Khurshid Ali (Archives of Business Research, 2021)
In this study, an investigation has been undertaken to determining the impact of Stock options trading on the volatility of underlying stocks. In order to achieve the objectives of the study, the researcher has taken into consideration six stocks on which options contracts were available throughout the reference period. The reference period of the study comprises of fourteen years that is divided into two periods namely, pre-derivatives and post-derivatives period. The pre-derivatives period comprises of seven years from 1995 to 2001 and it is the period during which stock options were not available in the stock market of India. The post-derivatives period also comprises of seven years (2002-2008) and it is the period during which stock options were available on the sample stocks. The researcher employed standard deviation to confirm the volatility effects of stock options and after the statistical analysis, the study affirmed an increase in the level of volatility in the post-derivatives period. Thus, it can be concluded, on the basis of the comparative analysis of statistical scores that the introduction of stock options trading have a definite impact on the volatility of the underlying stocks as the volatility levels registered upward trajectory throughout the post-derivatives period as compared to pre-derivatives period.